Sortilin knock-down alters the expression and distribution of cathepsin D and prosaposin and up-regulates the cation-dependent mannose-6-phosphate receptor in rat epididymal cells - Aguilera, Andrea Carolina (2023)
The selective transport to lysosomes can be mediated by either mannose-6-phosphate receptors (CD-MPR and CI-MPR) or sortilin. In mammalian epididymis, some lysosomal proteins are secreted into the lumen through unknown mechanisms. To investigate the underlying mechanisms of lysosomal protein transport in epididymal cells we studied the expression and distribution of cathepsin D (CatD) and prosaposin (PSAP) in a sortilin knocked down RCE-1 epididymal cell line (RCE-1 KD) in comparison with non-transfected RCE-1 cells. In RCE-1 cells, CatD was found in the perinuclear zone and co-localize with sortilin, whereas in RCE-1 KD cells, the expression, distribution and processing of the enzyme were altered. In turn, PSAP accumulated intracellularly upon sortilin knock-down and redistributed from LAMP-1-positive compartment to a perinuclear location, remaining co-localized with CatD. Interestingly, the sortilin knock-down induced CD-MPR overexpression and a redistribution of the receptor from the perinuclear zone to a dispersed cytoplasmic location, accompanied by an increased co-localization with CatD. The increase in CD-MPR could result from a compensatory response for the proper delivery of CatD to lysosomes in epididymal cells. The intracellular pathway taken by lysosomal proteins could be an approach for addressing further studies to understand the mechanism of exocytosis and therefore the role of these proteins in the epididymis.